Sodium Citrate Electrolyte Additive to Improve Zinc Anode Behavior in Aqueous Zinc-Ion Batteries - Xin Liu; Liang Yue; Weixu Dong; Yifan Qu; Xianzhong Sun; Lifeng Chen (Batteries, 2024)
Despite features of cost-effectiveness, high safety, and superior capacity, aqueous zinc-ion batteries (ZIBs) have issues of uncontrolled dendritic cell failure and poor Zn utilization, resulting in inferior cycling reversibility. Herein, the environmentally friendly and naturally abundant sodium citrate (SC) was adopted as a dual-functional additive for ZnSO4-based (ZSO) electrolytes. Owing to the abundant hydrogen-bond donors and hydrogen-bond acceptors of SC, the Zn2+-solvation shell is interrupted to facilitate Zn desolvation, resulting in inhibited corrosion reactions. Additionally, sodium ions (Na+) from the SC additive with a lower effective reduction potential than that of zinc ions (Zn2+) form an electrostatic shield inhibiting the formation of initial surface protuberances and subsequent Zn dendrite growth. This assists in the Zn three-dimensional (3D) diffusion and deposition, thereby effectively enhancing cycling stability. Specifically, a long cycling lifespan (more than 760 h) of the Zn//Zn symmetric cell is achieved with a 2 M ZSO-1.0 SC electrolyte at a current density of 1 mA cm−2. When coupled with the NaV3O8·1.5 H2O (NVO) cathode, the full battery containing SC additive exhibited a capacity retention rate (40.0%) and a cycling life of 400 cycles at a current density of 1 A g−1 compared with that of pure ZnSO4 electrolyte (23.8%). This work provides a protocol for selecting an environmentally friendly and naturally abundant dual-functional electrolyte additive to achieve solvation shell regulation and Zn anode protection for the practical large-scale application of ZIBs.